Anesthesiology In-Training Exam Review Regional Anesthesia and Chronic Pain - Banik, Ratan K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Focused on rotations in regional anesthesia and chronic pain, this book provides a structured review of the concepts covered in the American Board of Anesthesiology in-training exam. The first section of the book covers regional anesthesia with dedicated chapters on basic science, acute postoperative pain, and nerve blocks for neuraxial, lower and upper extremity blocks, and head and neck. The second section on chronic pain includes chapters on basic science and common pain conditions - including craniofacial pain, CRPS, neuropathic pain, and cancer pain. This section closes on multimodal analgesia and other treatment approaches. Each chapter presents a common clinical topic and is organized by indications, preparation, technique, complication, prevention, clinical pearls, and related ABA key points. Highlights must-know information in bold throughout the text. Concise, practical, and easy-to-read, this book will aid anesthesiology residents, certified nurse anesthetists, and medical students in their study regarding patient care practices on regional anesthesia and chronic pain. The book will also be useful to residents going into regional anesthesia and pain medicine subspecialties during the year of their anesthesiology training. .
Basic science:Principles of Ultrasound: Obtaining an Image, Resolution, Depth-Basic science: Local anesthetics and adjuvants for nerve blocks-Acute postoperative pain: Patient-Controlled Analgesia-Acute postoperative pain: Regional vs General anesthesia-Acute postoperative pain: Pediatric Regional Anesthesia-Regional Anesthesia for Enhanced Recovery After Surgery-Nerve injury in regional anesthesia-Bier block-Local anesthetic systemic toxicity -- Post-Dural Puncture Headache -- Spine anatomy; Epidural (Cervical, Thoracic, Lumbar, Caudal) -- Epidural adjuvants -- Spinal and combined spinal epidural -- Somatic and autonomic blockade-ASRA Guidelines on Implications of Anticoagulants and Platelet Inhibitors-Sciatic nerve block and Lateral Femoral Cutaneous nerve block-Femoral Nerve Block and Adductor Canal Block-Lumbar Plexus Block And Obturator Nerve Block-Popliteal Sciatic Block-Ankle Block -- Interscalene and superior trunk block-Supraclavicular nerve block-Infraclavicular and Axillary nerve block-Wrist blocks: Ulnar, Radial, Median nerve blocks-Suprascapular nerve block- Intercostal nerve block-Transversus Abdominis Plane Blocks-Thoracic paravertebral nerve block- Ilioinguinal and iliohypogastric nerve block-Erector spinae block -- Pectoralis nerve block -Glossopharyngeal, Superior Laryngeal, Transtracheal block- Retrobulbar block and Peribulbar block-Superficial Cervical Plexus Block for awake carotid endarterectomy- Pain Mechanisms and Pathways -- Opioid Receptors -- Social, Vocational and Psychological Influences on Pain Perception-Gender and Age Differences in Pain Perception-Pathophysiology of acute and chronic pain; somatic vs visceral pain-Myofascial Pain syndrome-Fibromyalgia-Headache and Botulinum Neurotoxins-supraorbital, infraorbital, auriculotemporal nerve block-Trigeminal Neuralgia-Occipital Neuralgia and Nerve Block-Stellate ganglion block-Celiac plexus nerve block and neurolysis-Lumbar Sympathetic block-Genitofemoral nerve block -- Pudendal nerve block-Neuroablation Techniques for Pain Management-Spinal Cord Stimulation and intrathecal drug delivery system-Transcutaneous Electrical Nerve Stimulation -- World Health Organization Analgesic Ladder-NSAIDs and Acetaminophen for Acute and Chronic Pain-Antidepressants and Anticonvulsants for Neuropathic pain-Opioid Analgesics, Tolerance, Dependence and Addiction-Equianalgesic doses of opioids-NMDA blocker: Methadone and Ketamine-Non-pharmacological approaches to chronic pain management.
Keywords: Anesthesiology; Pain medicine; Anesthesiology; Pain Medicine